Respuesta :

Answer:

Part A)

The equation in the point-slope form is:

[tex]y-11=\frac{4}{3}\left(x-\left(-2\right)\right)[/tex]

Part B)

The graph of the equation is attached below.

Step-by-step explanation:

Part A)

Given

  • The point = (-2, 11)
  • m = 4/3

The point-slope form of the line equation is

[tex]y-y_1=m\left(x-x_1\right)[/tex]

Here, m is the slope and (x₁, y₁) is the point

substituting the values m = 4/3 and the point (-2, 11)  in the point-slope form of the line equation

[tex]y-y_1=m\left(x-x_1\right)[/tex]

[tex]y-11=\frac{4}{3}\left(x-\left(-2\right)\right)[/tex]

Thus, the equation in the point-slope form is:

[tex]y-11=\frac{4}{3}\left(x-\left(-2\right)\right)[/tex]

Part B)

As we have determined the point-slope form which passes through the point (-2, 11) and has a slope m = 4/3

The graph of the equation is attached below.

Ver imagen absor201